Role of Effective Corporate Governance and Motivational Leadership in Increasing Productivity and Efficiency of Human Resources - Mohammad Mahfuzul Islam Chowdhury; Khatijah Othman; Mohammad Aktaruzzaman Khan; Ibrahim Fahad Sulaiman (Global Journals Inc., 2024)
Non-Indexed Publication